New insights into microRNAs in skin wound healing. Issue 12 (23rd November 2015) - Fahs, Fatima; Bi, Xinling; Yu, Fu‐Shin; Zhou, Li; Mi, Qing‐Sheng
Abstract: Chronic wounds are a major burden to overall healthcare cost and patient morbidity. Chronic wounds affect a large portion of the US, and billions of healthcare dollars are spent in their treatment and management. microRNAs (miRNAs) are small, noncoding double‐stranded RNAs that post‐transcriptionally downregulate the expression of protein‐coding genes. Studies have identified miRNAs involved in all three phases of wound healing including inflammation, proliferation, and remodeling. Some miRNAs have been demonstrated in vitro with primary keratinocyte wound healing model and in vivo with mouse wound healing model through regulation of miRNA expression to affect the wound healing process. This review updates the current miRNAs involved in wound healing and discusses the future therapeutic implications and research directions. © 2015 IUBMB Life, 67(12):889–896, 2015